Hubungan antara Health Locus of Control dan Self Efficacy dengan Kepatuhan Minum Obat Pasien Diabetes Mellitus Tipe II - Farraz, Deisya Alif; Setiasih, Setiasih (Universitas Muhammadiyah Metro, 2025)
This study aims to determine the relationship between Health Locus of Control and Self Efficacy with Mediation Adherence. The health locus of control measured is the internal aspect of HLC, powerful others HLC, and chance HLC. This research was conducted on people with type II diabetes mellitus. The data collection tools are an adaptation scale questionnaire by Damayanti and the MHLC scale developed by Wallston. Data analysis was carried out using Spearman’s Rho statistical techniques with the help of SPSS 26.0 for Windows. Based on the results of data analysis, it was found that health locus of control and self-efficacy were not related to mediation adherence (r = 0.046; p > 0.05). the results of this analysis show that health locus of control and self-efficacy are not related to medication adherence.